1989
DOI: 10.1007/bf00914309
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione in bronchoalveolar lavage fluid from smokers is related to humoral markers of inflammatory cell activity

Abstract: Cigarette smoking results in variable degrees of inflammation in the lower respiratory tract. Furthermore, smoking produces oxidant-mediated changes in the lung, important to the pathogenesis of emphysema. Since glutathione can neutralize reactive oxygen species and prevent peroxidation of unsaturated lipids, it may constitute an important component of the lung's defense against oxidant and inflammatory injury. In the present study, broncholaveolar lavage (BAL) was performed in 27 smokers, and the concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 17 publications
2
32
0
Order By: Relevance
“…These studies suggest that GSH plays a critical role in maintaining epithelial membrane integrity and may protect epithelial cells against the inflammatory response produced by either inhaled or endogenous oxidants/free radicals. Furthermore, LINDEN and coworkers [204,205] demonstrated that airway obstruction, measured by means of the forced expiratory volume in one second (FEV1) in patients with COPD, correlated significantly with the concentration of GSH in BALF; the higher the BALF GSH, the lower the FEV1. It may be that the BALF GSH levels were influenced by the recent smoking history of these patients [24].…”
Section: Antioxidant Protective Genesmentioning
confidence: 99%
“…These studies suggest that GSH plays a critical role in maintaining epithelial membrane integrity and may protect epithelial cells against the inflammatory response produced by either inhaled or endogenous oxidants/free radicals. Furthermore, LINDEN and coworkers [204,205] demonstrated that airway obstruction, measured by means of the forced expiratory volume in one second (FEV1) in patients with COPD, correlated significantly with the concentration of GSH in BALF; the higher the BALF GSH, the lower the FEV1. It may be that the BALF GSH levels were influenced by the recent smoking history of these patients [24].…”
Section: Antioxidant Protective Genesmentioning
confidence: 99%
“…However, there are adaptive responses in the antioxidant shield to chronic cigarette smoking. Chronic cigarette smokers have increased GSH in BAL fluid (111,112). This may be due to oxidant-mediated activation of the redox-sensitive transcription factor AP-1 (Figure 1), which upregulates expression of ␥-glutamylcysteine synthetase, the rate-limiting enzyme in GSH synthesis (113,114).…”
Section: Evidence Of Increased Oxidative Stress In Copdmentioning
confidence: 99%
“…There is limited information about respiratory epithelial antioxidant defenses in smokers, and even less about those in patients with COPD. Studies have shown that glutathione is elevated in BALF from chronic smokers (64,75). Even so, glutathione may not be present in sufficient quantities to deal with the excessive oxidant burden during acute smoking, as cigarette smoke exposure depletes glutathione in a dose-and time-dependent manner (76).…”
Section: Role Of Oxidants and Antioxidants In Smoking-induced Copdmentioning
confidence: 99%